Improving Clinical Outcomes in Newly Diagnosed Pediatric Type 1 Diabetes: Teamwork, Targets, Technology, and Tight Control—The 4T Study - Prahalad, Priya; Zaharieva, Dessi P.; Addala, Ananta; New, Christin; Scheinker, David; Desai, Manisha; Hood, Korey K.; Maahs, David M. (Frontiers in Endocrinology, 2020)
Many youth with type 1 diabetes (T1D) do not achieve hemoglobin A1c (HbA1c) targets. The mean HbA1c of youth in the United States is higher than much of the developed world. Mean HbA1c in other nations has been successfully modified in other nations following benchmarking and quality improvement methods. In this review, we describe the novel 4T Approach -Technology, Teamwork, Targets, and Tight Control -to diabetes management in youth with new onset T1D. In this program, the diabetes care team (physicians, nurse practitioners, certified diabetes educators, dieticians, social workers, psychologists, and exercise physiologists) work closely to deliver diabetes education from diagnosis. Part of the education curriculum involves early integration of technology, specifically CGM, and developing a curriculum around using the CGM to maintain tight control and optimize quality of life.